Simplicius Simplicissimus - Nel, Christof 1944-2024; Mahnke, Claudia 1967-; Aken, Frank van; Göhrig, Heinz; Ryan, Kwamé 1970-; Ebbecke, Michael 1955-; Munkittrick, Mark 1951-; Berger-Tuna, Helmut 1942-2009 (Arthaus Musik, 2007)
The boy Simplicius, a humble, bagpipe-playing shepherd lad set loose in a terrifying world of sacking and pillage, witnesses the devastation, class warfare, human disaster and carnage that universal war can bring.
Interpr. u.a.: Mahnke, Claudia (Simplicius). Aken, Frank van (The hermit). Göhrig, Heinz (The governor). Ebbecke, Michael (Landsknecht). Munkittrick, Mark (Hauptmann). Berger-Tuna, Helmut (Bauer). Württembergische Staatstheater <Stuttgart> / Chor. Staatsorchester Stuttgart. Ryan, Kwamé (Dir.). Christof Nel (Regie). - Prod.: SWR/BR/Arte 2005
Keywords: Operas; Filmed operas